Program Pra Nikah dalam Pendekatan Islam, Psikologi dan Finansial di Era Pandemi Covid-19 - Karimulloh Karimulloh; Chandradewi Kusristanti; Arif Triman (Lembaga Penelitian Universitas YARSI, 2020)
Islam views marriage as noble and sacred. In addition, marriage is one of the developmental tasks that a human being must go through. However, inadequate preparation from Islamic, psychological and financial perspective, led to the high number of divorce rate in Indonesia. This pre-marital education from the islamic, psychology and financial perspective carried out to increase knowledge about preparation for marriage according to islam and what preparation is needed to adolescent from the psychological view. So with this training, the participant can prepare a good marriage plan and take on responsibilities in marriage. Participants in this training are late teenagers and unmarried young adults. The results showed that there was an increase in the participants' knowledge of pre-marital education from Islamic, psychological and financial perspective.of papers should describe briefly the importance of the community service and reasonable.Abstract is a representation of the contents of the document are short and precise.Abstract presenting the problem, the information and methods used to solve the problem of your community service and conclusions. This should only contain important matters only and not exceed 200 words. The use of the reference citations should be avoided